2016
DOI: 10.20855/ijav.2016.21.3416
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on a High-Frequency Controller for Rotor BVI Noise Alleviation

Abstract: Among the several sources of acoustic annoyance produced by rotorcraft in operating conditions, blade-vortex interactions (BVIs) capture the interest of much of the current research. This paper deals with the reduction of BVI noise from helicopter main rotors by application of the active twist rotor concept (ATR), exploiting smart materials for twisting blades through higher-harmonic torque loads. An optimal, multi-cyclic, control approach is applied to identify the control law driving the ATR actuation during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Active rotor control has been studied for several years, but most studies were for blade-vortex interaction (BVI) noise. It can be achieved through higher harmonic control [8][9][10], individual blade control [11][12][13], active flaps [14][15][16][17], and active twist [18][19][20]. The numerical and test results demonstrate that the active rotors are effective for BVI noise and vibration reduction as well as performance enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…Active rotor control has been studied for several years, but most studies were for blade-vortex interaction (BVI) noise. It can be achieved through higher harmonic control [8][9][10], individual blade control [11][12][13], active flaps [14][15][16][17], and active twist [18][19][20]. The numerical and test results demonstrate that the active rotors are effective for BVI noise and vibration reduction as well as performance enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…The latter, like higher harmonic control (HHC), individual blade control (IBC), or active trailingedge flap control, use relatively low-frequency actuation inputs to produce blade response by increasing the miss distance i.e., the relative distance between vortex and blade, thus alleviating BVI effects. However, the success of these techniques, shown to be capable of considerable BVI noise reduction, [1][2][3][4] often corresponds to increased rotor vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on an optimal linear-quadratic multi-cyclic local controller capable of generating anti-BVI loads through multi-harmonic pitch motion of a suitable blade portion, that procedure offered the opportunity of reducing BVI noise without the drawback of structural vibrations. 4,5 Numerical investigations have shown promising results, although suggesting further developments concerning its feasibility and the efficiency of the process for control law determination. These two issues are examined in the present work, with the introduction of realistic control actuation devices on the blade, and with the application of an efficient semi-analytical method for the controller identification.…”
Section: Introductionmentioning
confidence: 99%
“…The actuation harmonics were those of BVI loads, with amplitudes given by a closed-loop control law determined through an optimal linear-quadratic multi-cyclic controller, efficiently synthesized by exploiting two-dimensional (2D) equivalent parallel BVI problems. A similar approach based upon an individual blade high-frequency controller, exploiting active twist actuation to reduce BVI rotor noise, has been also proposed and investigated in Anobile et al 15,16 . Numerical solutions presented in Modini et al [12][13][14] and Anobile et al 15,16 have shown promising results, suggesting the need of further developments and investigations aimed at assessing the feasibility of such kind of control approach.…”
Section: Introductionmentioning
confidence: 99%
“…A similar approach based upon an individual blade high-frequency controller, exploiting active twist actuation to reduce BVI rotor noise, has been also proposed and investigated in Anobile et al. 15,16 . Numerical solutions presented in Modini et al.…”
Section: Introductionmentioning
confidence: 99%